Producing Black Pepper (Piper Nigrum L. cv. ‘Kuching’) Rootstock in a Deep-Water Culture Hydroponic System - King, Jie Hung; Khadijah, Babirye; Ong, Kian Huat (Borneo Journal of Resource Science and Technology, 2021)
Stem cutting is the common planting material for black pepper (Piper nigrum L.) farmers mainly because the method is cheap, easy to obtain, and produces satisfactory number of new plantlets, which are relatively genetically uniform to their parent. However, soil propagation of stem cuttings renders both the stem and developing roots susceptible to soil borne pathogens, ultimately compromising the quality of the plant. Good quality rootstock of the new plant promotes faster, safer, and better black pepper plant establishment. Hydroponic farming thus offers a good platform for producing quality rootstock of the new plants and has gained importance to many farmers due to its flexibility in manipulating plant growth conditions and timely pathogen management, thus safer, healthier, and faster growth. This study investigated the growing media suitable for rootstock growth of P. nigrum L. cv. ‘Kuching’ and compared the rooting ability between stem cuttings with adventitious roots at the time of planting and stem cuttings without any root at the time of planting. In a laboratory setting, a total of 210 stem cuttings were hydroponically planted in seven nutrient compositions, with each nutrient composition containing an equal number of stem cuttings with adventitious roots at the time of planting and stem cuttings without any root at the time of planting. Hoagland solution supplemented with 0.005 mM potassium silicate solution (T4) and Hoagland solution supplemented with 2 mM salicylic acid solution (T6) showed faster root initiation whereas T1 (Hoagland solution only) produced the highest increment in root length followed by T6. The least suitable nutrient composition was T5 [T4 + 6 mL of 1 M Ca (NO3)2.4H2O solution]. The total number of roots was highest in plants from stem cuttings which had some adventitious roots at the time of planting, whereas roots in plants from stem cuttings which did not have any root at the time of planting, increased in root length faster than plants withstem cuttings which had adventitious roots at the time of planting.